Guided by the beauty of our weapons: comparing project management standards inside and outside international development. Issue 7 (2nd October 2020) - Munro, Lauchlan T.; Ika, Lavagnon
ABSTRACT: In order to identify their different knowledge areas, concepts, tools and emphases, this article compares project management standards from two non-profit, one parastatal and two governmental organisations working in international development against the standards of the Association for Project Management (APM) and the Project Management Institute (PMI). It finds that the international development and non-international development standards have quite different ideas of what project management entails. International development standards emphasise beneficiary participation, environmental impact, gender, unintended consequences of projects, soft objectives, evaluation techniques, and cross-cultural issues more than the APM or PMI standards. The latter standards have strengths in scoping and scheduling.